The Power of Influencer Endorsements: Uniting Stimuli-Organism-Response Theory with Information Adoption Insights - Rahmani, Shinta; Juniarti, Septiani; Sardiana, Anna; Puspita, Puspita (Yayasan Riset dan Pengembangan Intelektual, 2024)
This study explores the effectiveness of influencer marketing on social media, with a focus on Instagram, by examining the impact of high-quality information and influencer credibility on consumer purchase intentions. Using a quantitative approach and Partial Least Squares Structural Equation Modeling (PLS-SEM), the research analyzes data from 216 respondents to assess the relationships between information quality, source credibility, sponsorship disclosure, information usefulness, and purchase intention. The findings reveal that high-quality information significantly influences information usefulness, which in turn, affects information adoption and ultimately impacts purchase intention. Notably, information adoption mediates the relationship between information usefulness and purchase intention, though its effect size is relatively modest. The results suggest that while sponsorship disclosure might influence perceptions, credible influencers who provide valuable content can effectively drive consumer engagement and purchasing decisions. Marketers are advised to collaborate with reputable influencers and ensure regular updates of high-quality content to maximize the impact on consumer behavior.